GDNF and the RET Receptor in Cancer: New Insights and Therapeutic Potential - Mulligan, Lois M. (Frontiers in Physiology, 2019)
The Glial cell line-derived neurotrophic Family Ligands (GFL) are soluble neurotrophic factors that are required for development of multiple human tissues, but which are also important contributors to human cancers. GFL signaling occurs through the transmembrane RET receptor tyrosine kinase, a well-characterized oncogene. GFL-independent RET activation, through rearrangement or point mutations occurs in thyroid and lung cancers. However, GFL-mediated activation of wildtype RET is an increasingly recognized mechanism promoting tumour growth and dissemination of a much broader group of cancers. RET and GFL expression have been implicated in metastasis or invasion in diverse human cancers including breast, pancreatic, and prostate tumours, where they are linked to poorer patient prognosis. In addition to directly inducing tumour growth in these diseases, GFL-RET signaling promotes changes in the tumour microenvironment that alter the surrounding stroma and cellular composition to enhance tumour invasion and metastasis. As such, GFL RET signaling is an important target for novel therapeutic approaches to limit tumour growth and spread and improve disease outcomes.